Implementasi Kebijakan Pengembangan Kawasan Cagar Budaya Kayutangan di Kota Malang - Harnani; Agus Suryono; Ike Wanusmawatie (Jurnal Bina Praja, 2025)
The Kayutangan area in Malang City holds historical, socio-cultural, and economic value, recognized as a heritage district with unique appeal. However, the excessive modernization of the area, primarily driven by the private sector, has begun to erode the existence of heritage buildings and local values, posing a significant challenge to heritage preservation. In response, the Malang City Government has implemented policies focusing on preservation and development, including slum area reduction, infrastructure revitalization, and local tourism growth. Despite these efforts, gaps remain in managing the sustainability of heritage values in the face of modernizing pressures. This study explores the implementation of the Kayutangan Heritage Area development policy through Grindle (2017) policy implementation framework, focusing on policy content and outcomes. A qualitative descriptive approach was used, including semi-structured interviews, observations, and documentation. Data was analyzed using qualitative coding, involving collection, categorization, and conclusion drawing. The study found that while the policy has led to positive impacts such as slum reduction, improved infrastructure, increased MSMEs, higher tourist visits, and historical preservation, challenges to sustainability emerged. These include modernization misaligned with the heritage theme and a lack of clear regulations on visual design, which undermine the area’s heritage branding. The absence of dedicated management authority and weak coordination among local government agencies also hinder effective intervention. The study recommends strengthening regulations by establishing a dedicated heritage area management authority and expanding the policy’s impact to ensure long-term development sustainability and a more equitable distribution of benefits.